Evaluation of Distribution Transformer Placement Optimal Based on Load Balance - Triwiyatno, Aris; Winardi, Bambang (International Journal of Global Sustainable Research, 2024)
The distribution system is divided into primary and secondary distribution networks. The primary distribution network is the network from the main substation transformer (GI) to the distribution substation, while the secondary is the channel network from the distribution substation transformer to the consumer or load. The primary distribution network is better known as the medium voltage network (JTM 20kV) while the secondary distribution is the low voltage network (JTR 220/380V). The distribution network is the part of the electric power system that is closest to customers or loads compared to the transmission network. Currently, network electricity conditions throughout Indonesia are experiencing a decline of 5% which is due to various factors such as the medium-scale diameter of the conductors used, so at the farthest SR the value of overvoltage is 10%, the allowable voltage drop and must anticipate an increase in electrical load of 22.7 %, the placement of the transformer is not optimal and the distance the electrical energy travels from the transformer to the load is not paid enough attention so that the capacity of a transformer is not optimal and the voltage drop is also greater. Given these conditions, re-evaluation and planning is needed that takes into account planning criteria such as allowable voltage drops and continuity of electricity services so that optimization of the network used can emerge.